Evidence-Based Design in Hospital Renovation Projects: A Study of Design Implementation for User Controls. (April 2020) - Bingham, Evan; Whitaker, David; Christofferson, Jay; Weidman, Justin
Purpose: The purpose of this article was to investigate and report the implementation of evidence-based design (EBD) principles relating to user controls into hospital renovation projects. Background: Progress requires the application of the most recent knowledge and technology. When it comes to the design and construction of healthcare facilities, the latest knowledge comes in the form of EBD research. EBD is the process of basing decisions about the built environment on credible research to achieve the best possible outcomes. The desired outcomes of EBD recommendations include improvements to enhance user control. User control factors include the individual control over bed position, air temperature, lights, sound, and natural light. Method: A list of recommendations from existing EBD literature related to user controls was compiled. Construction documents from 30 recent healthcare facility renovation projects across the United States were obtained and analyzed. Implementation levels for the EBD categories of user controls were reported. Results: The findings indicate relatively extensive industry use of EBD principles relating to user control of temperature, lights, and natural lighting. Conclusions: The findings indicate that EBD recommendations related to user controls are being adopted in practice at consistently high levels. These findings also reveal that there are still areas of potential improvement which could inform those who influence or determine building design, codes, standards, and guidelines. The results are helpful to owners, designers, and contractors by providing a glimpse into how well the industry is recognizing and implementing known best practices. The findings likewise introduce new opportunities for further research which could lead to additional improvement in the healthcare facilities of the future.